-7-9k=7-7k

Simple and best practice solution for -7-9k=7-7k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7-9k=7-7k equation:


Simplifying
-7 + -9k = 7 + -7k

Solving
-7 + -9k = 7 + -7k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '7k' to each side of the equation.
-7 + -9k + 7k = 7 + -7k + 7k

Combine like terms: -9k + 7k = -2k
-7 + -2k = 7 + -7k + 7k

Combine like terms: -7k + 7k = 0
-7 + -2k = 7 + 0
-7 + -2k = 7

Add '7' to each side of the equation.
-7 + 7 + -2k = 7 + 7

Combine like terms: -7 + 7 = 0
0 + -2k = 7 + 7
-2k = 7 + 7

Combine like terms: 7 + 7 = 14
-2k = 14

Divide each side by '-2'.
k = -7

Simplifying
k = -7

See similar equations:

| =2z^2+13z+15 | | (2/3x)+(4/3)=(-4/3) | | 3(x-2)=4x-2-2x+3 | | 3(2x-x)=18-1 | | 8-9x-2=-40+6x-14 | | -28-6y=2(-6y+1) | | x^2/5=32 | | y+(y-50)=180 | | =4v*3v^4u^6*2u^7 | | -4x-13=6x+17 | | 3+c+6= | | 9+4x=3(x+4) | | 4-6m=(3m+14)-2(3m+5) | | 1.2t+3.4=-1.0 | | 6y+14=-7-y | | 11-3(x-1)=6+x | | 4(4x-3)-6x=x | | 3-2x(x+1)=x-2 | | -x+4x+1=3x-1+2 | | -2x+2x+4=3x-2x+2 | | 6-8x-3=-39+6x-14 | | 80+x=180 | | -9(x-7)-6=57 | | -20-9b+1=16b+20 | | 2(6x+5)=3x-26 | | 3-19p=-18p+20 | | -6w-12+2w=28 | | (10/3)/(2/21) | | -4/-5y=72 | | -3m=-6-5m | | 52/650 | | (1/4x-6)=(2/3x+3) |

Equations solver categories